"Nobody Wants to Be an Outsider": From Diversity Management to Diversity Engagement. Issue 3 (28th June 2015) - Howarth, Caroline; Andreouli, Eleni
Abstract : This article develops an analysis of diversity in two ways. We start with a theoretical discussion of the ways in which diversity has been approached within psychology, showing the competing arguments that have been developed that connect diversity, community, and multiculturalism. We show that not only are there psychological consequences to contemporary experiences of increased diversity but also that fundamental psychological capacities—such as self‐consciousness, identity, and dialogue—actually stem from the experience of diversity. This has important implications for diversity management policies. The second part of the article gives an empirical illustration of how diversity is experienced in schools across England drawing on 13 interviews with senior staff and 11 focus groups with pupils aged between 12 and 14 years old. We discuss three themes related to experiences of diversity: (1) from difference to diversity, (2) real and imagined mobility across communities, and (3) collaborative practices, projects, and knowledge. What the empirical examples show is that critically engaging with diversity can be a more productive project than practices which construct diversity in terms of distinct groups that need respect and tolerance. Hence we argue approaches that promote engaging with diversity rather than traditional diversity management are more in line with foundational psychological insights as well as empirical research findings.